Zinc Deficiency-Associated Dysgeusia Preventing the Improvement of Severe Hyperemesis Gravidarum - Shohei Tanabe; Sachiyo Sugino; Kotaro Ichida; Kiyoshi Niiya; Syuji Morishima (Case Reports in Obstetrics and Gynecology)
A 23-year-old primigravida visited the hospital frequently since the early phase of her pregnancy because of severe hyperemesis gravidarum. She was hospitalized for the same at 14 weeks and 1 day of pregnancy. After admission, peripheral intravenous nutrition was started; however, her symptoms did not improve. At 17 weeks and 1 day of gestation, a blood sample was collected to determine the presence of trace element deficiencies, and a zinc deficiency was revealed. We examined the patient’s symptoms and found that she had developed dysgeusia. After receiving a zinc preparation, her taste disorder gradually improved, and her oral intake increased. Her hyperemesis gravidarum resolved, and she was discharged from the hospital at 18 weeks and 2 days of gestation. The findings from this case suggest that prolonged peripheral intravenous nutrition in patients with severe hyperemesis gravidarum can lead to zinc deficiency and impede the successful treatment of hyperemesis gravidarum.